Penerapan Ice Breaker dalam Strategi Pembelajaran Berbantu Kartu Pintar Terhadap Hasil Belajar Kelas I - Faisalina, Sonta Asilsa (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning class I SDN Ngarus 02 Pati. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 32 students in grade I SDN Ngarus 02 Pati for the 2019/2020 academic year. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of smart card assisted ice breakers can improve learning outcomes in theme 6 Subthemes 2 learning 1 grade 1 students of SDN Ngarus 02 Pati for the 2019/2020 school year as evidenced by the percentage of learning outcomes completeness in pre-cycle by 25% to 75% in cycle I and becomes 93% in cycle II.